English language, immersive teaching and game-based learning in a teacher training project promoted by Indire - Letizia Cinganotto (Firenze University Press, 2017)
The paper presents the results of an immersive training initiative in "Edmondo", a virtual world based on OpenSim technology provided by Indire and addressed to Italian teachers and students. The initiative aimed to close the gap of gaming virtual worlds and social virtual worlds through user-generated content created by teachers (primary and secondary English and CLIL teachers). The content created was language learning games, activities, simulations, scenarios, role-plays, designed to be used in a virtual environment. Currently these games and activities are on display in a games park setting readily available for teachers to take their young learners to and engage them in real-time and fun communication activities. This paper presents the development and the results of the methodology course conducted in 2016 delivered by a group of international experts: the initiative will be described with the help of the data collected through questionnaires, diaries, comments and a devoted virtual focus group.   Lingua inglese, didattica immersiva e game-based learning in un progetto di formazione per docenti promosso da Indire Il contributo presenta una iniziativa di formazione per docenti promossa da Indire nel 2016 sulla didattica immersiva della lingua inglese in "Edmondo", il mondo virtuale online dedicato alla scuola. Il progetto di ricerca sotteso alla formazione mirava a rilevare il potenziale della tecnologia immersiva e del game-based learning per l'apprendimento della lingua inglese e per l'applicazione della metodologia CLIL (Content and Language Integrated Learning). Il progetto si proponeva di creare un ponte tra gaming virtual worlds e social virtual worlds, mettendo in luce come le tecnologie immersive possano facilitare l'apprendimento e la comunicazione nella lingua straniera attraverso l'uso di giochi interattivi, scenari, ambienti simulati, role-play realizzati nel mondo virtuale dagli stessi partecipanti (docenti di lingua inglese e docenti CLIL di scuola primaria e secondaria), sotto la guida di esperti internazionali. Il progetto di ricerca viene descritto nelle sue molteplici sfaccettature, attraverso l'illustrazione degli ambienti di formazione, l'esame dei dati raccolti nei diari dei partecipanti, nei questionari e in un focus group dedicato.